The Development Of Digital Module Based in Mobile Learning on the History Learning Of Senior High Schools in Jember District by 4D Development Model - Hari Wahyudi; Nurul Umamah; Sri Handayani; Rully Putri Nirmala Puji (History Education, University of Jember, 2018)
Technological developments are increasingly rapidly encouraging the education innovatively to utilize and develop mobile phones for the purposes of learning, commonly known as term Mobile Learning. Mobile Learning can be defined as part of e-learning (electronic learning) which the delivery of the material is done with the help of telecommunication tools. The results of needs assesment of learners at 5 senior high schools in Jember District, showed that 80% of teaching materials is limited to textbooks and 100% of students have mobile phones for communication only. This study aimed to overcome the curriculum gap and lack of utilization of technology, especially mobile for learning. The method used in this research is a quantitative method. The validation result of digital module development based on Mobile Learning showed the language validity of 80%, material content validity 84%, and design validity 87.5%. while the user test showed that 89%. It means that the learning materials is in effective level. This showed that the Mobile Learning-based digital module deserves to be an innovative resource for history learning. Keywords: History Learning, Mobile Learning, Digital Module Technological developments are increasingly rapidly encouraging the education innovatively to utilize and develop mobile phones for the purposes of learning, commonly known as term Mobile Learning. Mobile Learning can be defined as part of e-learning (electronic learning) which the delivery of the material is done with the help of telecommunication tools. The results of needs assesment of learners at 5 senior high schools in Jember District, showed that 80% of teaching materials is limited to textbooks and 100% of students have mobile phones for communication only. This study aimed to overcome the curriculum gap and lack of utilization of technology, especially mobile for learning. The method used in this research is a quantitative method. The validation result of digital module development based on Mobile Learning showed the language validity of 80%, material content validity 84%, and design validity 87.5%. while the user test showed that 89%. It means that the learning materials is in effective level. This showed that the Mobile Learning-based digital module deserves to be an innovative resource for history learning. Keywords: History Learning, Mobile Learning, Digital Module